Building cross-platform mobile and web apps for engineers and scientists an active learning approach - Lingras, Pawan; Triff, Matt; Lingras, Rucha (Cengage Learning, 2017)
Apps continue to evolve, but the technologies in this book form the backbone for future cross-platform app development. Students learn to work with all major mobile and web platforms as this book's active learning approach asks students to type code in parallel as the apps are developed. Meaningful exercises further encourage students to change code and evaluate resulting app behavior.